(untitled) (LEARNing Landscapes, 2011)
Inquiry in today’s classrooms has been reduced to a formula for learning the scientific method with any given topic, most often in science in elementary school.While there is value in acquiring a method for approaching a query, students are deprived of the opportunity to construct their own queries, to pursue their natural puzzlement over personal and real-world dilemmas. Questions arise about the value of this procedure in assisting students to develop facility with the genres of the disciplines.